2020
DOI: 10.1186/s13068-020-1659-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring why sodium lignosulfonate influenced enzymatic hydrolysis efficiency of cellulose from the perspective of substrate–enzyme adsorption

Abstract: Background: Cellulase adsorbed on cellulose is productive and helpful to produce reducing sugars in enzymatic hydrolysis of lignocellulose; however, cellulase adsorbed on lignin is non-productive. Increasing productive adsorption of cellulase on cellulose would be beneficial in improving enzymatic hydrolysis. Adding lignin that was more hydrophilic in hydrolysis system could increase productive adsorption and promote hydrolysis. However, the effect mechanism is still worth exploring further. In this study, lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…All extracted DAP-BR samples had a much lower zeta potential (absolute value) than DAP-BR. Higher zeta potential (absolute value) values for substrates represent higher surface charge and more hydrophilic substrates [ 36 , 37 ]. Furthermore, hydrophilic substrates also exhibit stronger electrostatic repulsion between lignin and cellulase, thereby reducing nonproductive binding of cellulase to lignin and enhancing enzymatic hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…All extracted DAP-BR samples had a much lower zeta potential (absolute value) than DAP-BR. Higher zeta potential (absolute value) values for substrates represent higher surface charge and more hydrophilic substrates [ 36 , 37 ]. Furthermore, hydrophilic substrates also exhibit stronger electrostatic repulsion between lignin and cellulase, thereby reducing nonproductive binding of cellulase to lignin and enhancing enzymatic hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, although it has been extensively reported that Fig. 4 Schematic diagram of cellulase adsorption on lignocellulose (DA-SCB) before and after adding LS (A) and schematic diagram of cellulase adsorption on pure cellulose (Avicel) before and after adding LS (B) [160] the formation of WSL-cellulase complexes can promote the enzymatic hydrolysis of lignin-containing substrates, it is not yet fully understood how complexes impacts the lignin-enzyme interaction, and thus the effect mechanism of WSL on lignocellulose still needs to be further explored.…”
Section: Mechanisms Of Interactions On Wsl and Cellulasementioning
confidence: 99%
“…Higher zeta potential (absolute value) values for substrates represents higher surface charge and more hydrophilic substrates. [32][33] Thus, more hydrophilic substrates also undergo stronger electrostatic repulsion between lignin and cellulase, reducing non-productive binding between lignin and cellulase to improve enzymatic hydrolysis.…”
Section: Influence Of Organic Extraction Agent On Enzymatic Digestibimentioning
confidence: 99%